PENGARUH STRATEGI PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV MI NIDHOMIYAH JOMBANG - Faridatul Masruroh; Tomi Syafrudin (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
Selection of appropriate learning strategies by teachers tailored to the subject matter, so that students can understand the subject clearly. Reciprocal Teaching is a learning strategy so that learning objectives are reached quickly through the process of independent learning. By presentation in front of a class, students are expected to achieve learning objectives and increase learning independence. This study aims to determine whether there is an influence of Reciprocal Teaching towards mathematics learning outcomes of fourth-grade students MI Nidhomiyah Jombang academic year 2018/2019. The calculation of the t-value uses SPSS 16. The result of t-value is 4,667 with sig (2 tailed)= 0,000. The data result showed that is rejected. The researchers concluded that there is influence Reciprocal Teaching towards mathematics learning outcomes.